Efektivitas Pengembangan Digital Bisnis pada Gen-Z dengan Model Bisnis Canvas - Nur Saebah; Muhamad Zaenal Asikin (Jurnal Syntax Transformation, 2022)
The development of Industry 4.0 that is currently happening greatly affects the creative economy in Indonesia which has begun to move towards the digital economy which is expected to be filled by young entrepreneurs who are creative, innovative and modern so that they can withstand the changes that will occur. In this case, the digital development of this business is very rampant in the Gen-Z era. The type of research used is qualitative research often called the naturalistic research method because the research is carried out in natural conditions. Data collection in this study was carried out in several stages. The first determines the topics and problems, the second is to search for literature studies through Google Scholar using digital business keywords, canva business methods and Gen-Z. The analytical technique used in this study is analytical analysis. Hasil this research states that the effectiveness of digital business development with a canvas business model is very good for Gen-Z to optimize. This is expected to be an alternative for Gen-Z digital business people in running micro-businesses such as online business ventures. Determining and choosing a good business strategy tool is important so that a company can survive and can develop its business in the midst of very tight business competition.